CO2-free power generation employing integrated ammonia decomposition and hydrogen combustion-based combined cycle. (1st October 2020) - Juangsa, Firman Bagja; Darmanto, Prihadi Setyo; Aziz, Muhammad
Highlights: Integrated system of NH3 decomposition and H2-based power generation is proposed. Heat circulation is performed based on the principle of enhanced process integration. Temperature and conversion rate influence both total and power generation efficiencies. The conversion rate effects the system efficiency due to amount of produced H2. Treaction temperature has a major effect on the power generation efficiency. Abstract: Despite the potential of hydrogen (H2 ) as an energy carrier, its storage and transportation are challenging and become two of the keys in the successful adoption of H2 . Among various methods of H2 storage, ammonia (NH3 ) shows very promising characteristics of high gravimetric and volumetric H2 densities, possibility for direct utilization, and established infrastructure. This work proposes an integrated system consisting of NH3 decomposition through a thermo-catalytic process and H2 -based power generation. The thermal energy demanded for the endothermic reaction of thermo-catalytic NH3 decomposition is supplied from the combustion reaction of H2 . The remaining heat is used to generate the electricity using a combined cycle, and the overall heat circulation is optimized based on enhanced process integration (EPI) to achieve a highly efficient system. Four types of catalyst (ruthenium, molybdenum nitride, nickel oxide, and lithium nitrohydride), having different reaction temperature and conversion rate, are employed in the system and their performance are then evaluated. The results show that both parameters have an influence in determining the system efficiency and power generation efficiency with different behavior. The conversion rate has a strong effect on the system efficiency as it determines the amount of H2 produced from the NH3 decomposition process. Meanwhile, the reaction temperature has a major effect on the power generation efficiency. The proposed system with lithium nitrohydride shows the highest power generation efficiency of 43.7%, while the highest overall system efficiency of 48.3% can be achieved when ruthenium catalyst is employed.